Weak–strong uniqueness for a class of generalized dissipative weak solutions for non-homogeneous, non-Newtonian and incompressible fluids. (April 2022) - Woźnicki, Jakub
Abstract: We consider a system of PDEs describing a non-homogeneous, non-Newtonian and incompressible fluid in a space-periodic domain. We define the generalized dissipative weak solutions as well as give a proof of its existence, when the boundary data is provided. The main result of this work is the weak–strong uniqueness of the defined solutions.